PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF INFORMAL TIPE FORMULATE SHARE LISTENING CREATE TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VII.2 MTsN 12 PESISIR SELATAN - Siska Siska (Horizon, 2021)
This research is motivated by the low ability of students to understand mathematical concepts and students are not used to discussing. The research objective was to determine how the effect of the application of the formulate share listening create informal cooperative learning model on the understanding of the mathematical concepts of class VII.2 students of MTsN 12 Pesisir Selatan.This research is a descriptive quantitative research based on one shoot case study. The population in this study were students of class VII MTsN 12 Pesisir Selatan which consisted of 5 classes. The sampling technique was taken using purposive sampling, so that class VII.2 MTsN 12 Pesisir Selatan was chosen as the sempel class. The research instrument was the final test in the form of an essay and thereliability of . Where based on data analysis the value of the trial class.Based on the calculation results, it was found that the percentage of learning outcomes with the conceptual understanding indicator obtained by students while using the formulate share listening create informal cooperative learning model was quite good. 61%. So it can be concluded that by applying the informal cooperative learning model type formulate share listening create to the students' ability to understand mathematical concepts class VII.2 MTsN 12 Pesisir Selatan is quite good.